Antenatal Care Visits, Economic Status, and Nutritional Status of Pregnant Women on Stunting - Hani Septiani; Resna Litasari; Dini Ariani; Aulia Ridla Fauzi; Eris Risyani (Nurul Ilmi : Journal of Health Sciences and Midwifery, 2023)
Introduction: Stunting is a chronic malnutrition problem caused by insufficient nutritional intake for a long time due to improper feeding. Toddlers who are stunted have a decreased risk of intellectual ability and productivity, as well as an increased risk of developing degenerative diseases in the future. Stunting is caused by many factors, so it is necessary to evaluate the relationship between the incidence of stunting in children under five, including antenatal care visits, economic status, and the nutritional status of pregnant women. Objective: Stunting is one of the nutritional problems globally, especially in developing countries. The impact of stunting affects many aspects including disorders of gross and fine motor development, language development, and personal social. Method: This research is an analytical descriptive research. using a cross-sectional approach to assess risk factors for stunting. he population in this study were all mothers who had toddlers aged 24-60 months. The sampling technique used in this study was to use a purposive sampling technique of 40 mothers of toddlers. The economic status of the family has a significant influence on the incidence of stunting as evidenced by the p-value <0.05.  Result: The statistical results show that the ANC has a significant effect on the incidence of stunting as evidenced by the p-value <0.05. The nutritional status of the mother based on MUAC has no significant effect on the incidence of stunting as evidenced by the p-value > 0.05 Conclusion: ANC visits, nutritional status and family economic status have a significant influence on the incidence of stunting in toddlers in Petirhilir Village, Working Area of the Baregbeg Health Center, Ciamis Regency.